Testing the extreme male hypothesis in the valproate mouse model; sex-specific effects on plasma testosterone levels and tyrosine hydroxylase expression in the anteroventral periventricular nucleus, but not on parental behavior - Grgurevic, Neza (Frontiers in Behavioral Neuroscience, 2023)
Autism is a neurodevelopmental disorder that begins very early in life and affects the most important aspects of human behavior - the ability to be social. Autism is most likely a multifactorial disorder with possible environmental, hormonal, autoimmune, genetic, and epigenetic contributions. It is one of the most sexually dimorphic neuropsychiatric disorders, more prevalent in males than females. Environmental factors such as the antiepileptic drug valproic acid (VPA) can induce autism-like traits in humans and rodents when exposed during gestation. Although many studies have been conducted in rodents exposed to VPA, the relationship between sex, gonadal hormones, and autism is still not clear. We show for the first time that prenatal VPA exposure can affect gonadal hormones and the enzyme tyrosine hydroxilase in one of the brain regions important for regulating sex-specific physiology and behavior, and that this effect is specific to males. Interestingly, parental behavior, which is highly social and sexually dimorphic, was not affected. Our study provides some new insights into the relationships between brain, behavior, and sex steroids in the VPA mouse model. The results will contribute to the understanding of autism pathology and etiology, especially from the perspective of sex differences.